Cabin environment and air quality in civil transport aircraft - Zhou, Weiguo (Cranfield University, 2012)
The cabin environment of a commercial aircraft, including cabin layout and the quality of air supply, is crucial to the airline operators. These aspects directly affect the passengers’ experience and willing to travel. This aim of this thesis is to design the cabin layout for flying wing aircraft as part of cabin environment work, followed by the air quality work, which is to understand what effect the ECS can have in terms of cabin air contamination. The project, initially, focuses on the cabin layout, including passenger cabin configuration, seat arrangement and its own size due to the top requirements, of a conventional aircraft and further into that of a flying wing aircraft. The cabin work in respect of aircraft conceptual design is discussed and conducted by comparing different design approaches. Before the evaluation of cabin air quality, an overall examination of the main ECS components involved in the contaminants access will be carried on and, therefore, attempt to discover how these components influence the property of the concerned contaminants. By case study in the B767 ECS, there are some comments and discussions regarding the relationship between the cabin air contaminations and the passing by ambient environment. The thesis ends up with a conclusion explaining whether or not the contaminated air enters the occupants’ compartments on aircraft and proposing some approaches and engineering solutions to the continue research.
Keywords: Cabin layout; flying-wing aircraft; cabin air contamination; contaminants; ECS(environmental control system); air conditioning pack